A germline variant in the TP53 polyadenylation signal confers cancer susceptibility - Stacey, SN; Sulem, P; Jonasdottir, A; Masson, G; Gudmundsson, J; Gudbjartsson, D; Magnusson, O; Gudjonsson, SA; Sigurgeirsson, B; Thorisdottir, K; Ragnarsson, R; Benediktsdottir, K; et al. (2011)
To identify new risk variants for cutaneous basal cell carcinoma, we performed a genome-wide association study of 16 million SNPs identified through whole-genome sequencing of 457 Icelanders. We imputed genotypes for 41,675 Illumina SNP chip-typed Icelanders and their relatives. In the discovery phase, the strongest signal came from rs78378222[C] (odds ratio (OR) = 2.36, P = 5.2 ×-10 -17), which has a frequency of 0.0192 in the Icelandic population. We then confirmed this association in non-Icelandic samples (OR = 1.75, P = 0.0060; overall OR = 2.16, P = 2.2 ×-10 -20). rs78378222 is in the 3' untranslated region of TP53 and changes the AATAAA polyadenylation signal to AATACA, resulting in impaired 3'-end processing of TP53 mRNA. Investigation of other tumor types identified associations of this SNP with prostate cancer (OR = 1.44, P = 2.4 ×-10 -6), glioma (OR = 2.35, P = 1.0 ×-10 -5) and colorectal adenoma (OR = 1.39, P = 1.6 ×-10 -4). However, we observed no effect for breast cancer, a common Li-Fraumeni syndrome tumor (OR = 1.06, P = 0.57, 95% confidence interval 0.88-1.27). © 2011 Nature America, Inc. All rights reserved.